2018
DOI: 10.1016/j.ssmph.2018.08.009
|View full text |Cite|
|
Sign up to set email alerts
|

Socioeconomic variables explain rural disparities in US mortality rates: Implications for rural health research and policy

Abstract: ObjectivesRural disparities in age-adjusted mortality are growing in the United States. While socioeconomic variables have been found to explain significant variation in life expectancy across US counties, previous research has not examined the role of socioeconomic variables in explaining rural mortality disparities. The purpose of this study was to quantify the rural mortality disparity after controlling for socioeconomic variables.MethodsRecursive partitioning, or tree regression, was used to fit models pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 24 publications
1
55
1
Order By: Relevance
“…Growing rural–urban and within-rural disparities may reflect increasing inequities in any number of upstream social-structural factors, including educational attainment, which is becoming an increasingly important determinant of morality disparities (Hayward et al 2015 ); as well as material resources, opportunities for employment and upward mobility, social capital and integration (Yang et al 2011 ); housing quality, environmental quality, and the distribution of economic, educational, and/or social resources. In a study that covered 2004–2012, Long et al ( 2018 ) found that median income and percent poverty explained nearly all of the rural mortality disadvantage and argued that interventions targeting social determinants of health in rural areas must be prioritized. Importantly, all of these factors are influenced by politics and policy decisions at the national, state, and local levels.…”
Section: Discussionmentioning
confidence: 99%
“…Growing rural–urban and within-rural disparities may reflect increasing inequities in any number of upstream social-structural factors, including educational attainment, which is becoming an increasingly important determinant of morality disparities (Hayward et al 2015 ); as well as material resources, opportunities for employment and upward mobility, social capital and integration (Yang et al 2011 ); housing quality, environmental quality, and the distribution of economic, educational, and/or social resources. In a study that covered 2004–2012, Long et al ( 2018 ) found that median income and percent poverty explained nearly all of the rural mortality disadvantage and argued that interventions targeting social determinants of health in rural areas must be prioritized. Importantly, all of these factors are influenced by politics and policy decisions at the national, state, and local levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although we found no significant difference between rural and urban cancer survivors for health status, previous studies have shown substantial rural-urban differences in health status outcomes. A small rural sample size may have limited our power to detect statistically significant differences and limited our ability to complete stratified analyses by cancer type or socioeconomic status, which may help explain disparities in PA and health status [3,24,25]. However, it is important to highlight that 24.3% and 18.9% of cancer survivors in this study reported their physical and mental health, respectively, as 'not good' for one week or more in the past month, regardless of rural-urban residence.…”
Section: Discussionmentioning
confidence: 99%
“…Language barriers have the potential to increase the risk to Spanish-speaking populations who cannot understand the public health messages or who are unable to communicate with providers or testing centers (Macias Gil et al 2020). In rural communities, this may be exacerbated by decreased access to care, unstable internet capabilities, and decreased transportation options (Long, Hanlon, and Pellegrin 2018), and isolation may increase the difficulty accessing accurate information, especially in the presence of language barriers (Macias Gil et al 2020).…”
Section: Introductionmentioning
confidence: 99%